A high-linearity DC planar Ionic anemometer. (October 2015) - Zhou, Zhijian; Jones, John Dewey; Leung, Albert M.; Nie, Weirong; Wang, Xiaofeng
Abstract: A high-linearity DC planar ionic anemometer which can measure the airflow velocity of boundary-layers near a surface was constructed and tested. The differential anemometer described in this paper includes two symmetrical cathodes and one anode with a sharp tip. High voltage is applied to the anode to generate a symmetrical ionic discharge, and then the airflow deflects the symmetrical ion distribution and produces a differential current between the two cathodes. It can detect bidirectional airflow velocity and is more crash-resistant than traditional hot-wire anemometers. It has minimum impact on the airflow profile because of its thin-shape design and achieves high measurement accuracy. A series of tests have been done for the static characteristics and dynamic performance by changing structural parameters such as cavity depth, gap width, anode tip angle, cathode width and length. The results show that the cavity depth is the most important structural parameter since it has the greatest effect on the stability of the gas discharge, which is affected by ion mobility and friction between ions and the bottom of cavity. The gap width plays a decisive role in the current and sensitivity values. Besides, the uncertainties of the tests have been analyzed by introducing the error bars and the testing errors are in reasonable ranges. The anemometer is cost-effective and offers the possibility of building a MEMS version in the future. Highlights: The planar ionic anemometer has less impact on the airflow than 3-D version. The planar ionic anemometer offers better measurement accuracy. Small size provides good portability and its linearity is very good. It has a simple structure with no moving parts and can be mass-produced cheaply.